The expansion of doctoral education and the changing nature and purpose of the doctorate - Sarrico, Cláudia S. (2022)
Doctorate level attainment has increased significantly in developed economies. In 2019, the average share of 25–64-year-olds with a doctorate across the OECD was around 1%. However, if current trends continue, 2.3% of today’s young adults will enter doctoral studies at some point in their life. This essay starts by describing the expansion of doctoral education. It then reflects on the causes of this growth and the consequences for the nature and purpose of the doctorate. This reflection is mostly based on published research in Higher Education in the last 50 years and the author’s work on policy analysis for the OECD on this topic. The paper finishes with a research agenda on doctoral education and the career of doctorate holders.